2023
DOI: 10.1128/mra.00140-23
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Endophytic Bacteria Inhabiting Wild Daucus Seed Using 16S rRNA Gene Amplicon Sequencing

Abstract: We report a preliminary survey of the endophytic bacterial microbiota of seed from wild carrot ( Daucus carota ) using 16S rRNA gene amplicon sequencing. Actinobacteria , Bacteroidetes , Firmicutes , and Proteobacteria were the most abundant phyla detected, while Bacillus , Massilia , Paenibacillus , Pantoea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Using these primers, the authors reported a very low abundance of plant DNA amplification following quantitative PCR (qPCR) analysis. Similarly, Kumar et al (2023) reported only low levels of amplification of plant chloroplast DNA using 335F/769R for carrot seed microbiota analysis. However, in our study, 15% of reads from the shoot bacterial data set were attributed to plant DNA when using the 335F/769R primer pair.…”
Section: Reducing Plant Organelle Dna Amplificationmentioning
confidence: 99%
“…Using these primers, the authors reported a very low abundance of plant DNA amplification following quantitative PCR (qPCR) analysis. Similarly, Kumar et al (2023) reported only low levels of amplification of plant chloroplast DNA using 335F/769R for carrot seed microbiota analysis. However, in our study, 15% of reads from the shoot bacterial data set were attributed to plant DNA when using the 335F/769R primer pair.…”
Section: Reducing Plant Organelle Dna Amplificationmentioning
confidence: 99%